Compound Verbs in Atabetu'l-Hakayik - Merhan, Aziz (AHMET YESEVI UNIV, 2009)
Compound verbs are an area of Turkish yet to be enlightened. This study, a contribution in the way of a solution to this matter, is about compound verbs in Atabetu'l-Hakayik, Edib Ahmet's work of the 12(th) century, introduced by Re it Rahmeti Arat to the world of science. Although Arat states that very few auxiliary verbs are used in the work (four auxiliary verbs, which are bil-, u-, bir-, and tur), we think this information is inadequate. The verbs Arat names as auxiliary words are descriptive verbs to us. These kinds of verbs determine - in terms of aktionsart - the meanings of main verbs that have lost their real meanings and have taken a converb. According to our study, there are eight descriptive verbs in Atabetu'l-Hakayik. The other group of compound verbs consists of compound verbs where the first verb in adverb form is protodescriptive, and the real meaning is conveyed by the second verb.
Keywords: Atabetu'l-Hakayik; Karahanidish; compound verbs; descriptive verbs; protodescriptive verbs; Area Studies